Analisis pengembangan kepemimpinan pendidikan di SMP Islam Darussalam Kotagede Yogyakarta - Rahmadani, Luthfi Setya; Hasibuan, Anggi Hartati (Rafandha Press, 2023)
The purpose of this study is to analyze the leadership development carried out by Mr. Ussaid Uzza, S.Pd in developing his leadership as the Principal of SMP Islam Darussalam Kotagede Yogyakarta. This research uses qualitative research methods with case study shortfalls. The method of data collection uses interviews, observations and documentation. Data analysis uses data reduction, data display and drawing/verification or drawing conclusions. The results of this study explained that in developing leadership, principals participated in various activities such as the Independent Curriculum Implementation Workshop and the Principal Working Group (K3S). From the various activities that were participated in, these activities were included in leadership development through the Independet Study activity , which is an independent study activity carried out by the principal of SMP Islam Darussalam which aims to develop individual abilities in leading educational units by utilizing supporting resources such as various activities that he participates in. The advantages of independent study activities are able to improve the personality competence of the principal. The weakness of independent study is that it is only able to develop personality competencies and has not been maximized in developing managerial competencies, entrepreneurial competencies, supervisory competencies and social competencies.